Crude oil price determinants - Jochen Möbert (Technische Universität Darmstadt, Department of Law and Economics, 2007)
Based on monthly observations, I specify an econometric model capturing the driving forces behind the crude oil price series in recent years. A large set of covariates, such as supply and demand variables as well as futures market variables, is used to test the impact on the crude oil price. Current price movements are a result of scarce refining capacity and speculators betting on higher prices. The results also question OPEC's market power.
Keywords: C51; Q41; 330; Crude oil market; Econometric modelling; Erdölpreis; Ökonometrisches Modell; Varianzanalyse; Schätzung; Mineralölmarkt; Schätzung; Welt